Fingerprints and Floor Plans Construction for Indoor Localisation Based on Crowdsourcing - Santos, Ricardo (2019)
This research was supported by North Portugal Regional Operational Programme (NORTE 2020), Portugal 2020 and the European Regional Development Fund (ERDF) from European Union through the project Symbiotic technology for societal efficiency gains: Deus ex Machina (DEM), NORTE-01-0145-FEDER-000026.